KAMOLIDDIN BEHZOD ASARLARINING REALISTIK XUSUSIYATLARI ASOSIDA TALABALARDA ESTETIK TARBIYANI SHAKLLANTIRISH METODIKASI - Masharipova, X.F. (SCIENCE and SOCIETY, 2025)
This article discusses the realistic art of Kamoliddin Behzod and its educational features, as well as the issues of developing the spiritual and moral education of students.
Keywords: realistic art; spiritual and moral education; aesthetic education; artistic education; creative activity; perception; aesthetic taste